Manajemen Pengambilan Keputusan Dalam Relokasi Pedagang Pasar Rakyat - Diana Suita; Marina Elsera; Liza Fitriana (LPPM STIKOM Tunas Bangsa, 2020)
Every change of location can certainly cause problems for the environment and the personnel involved in it. This also happened in the case of relocation of Rajawali People's Traditional Marketing Pematang Siantar City. Many personnel involved in this relocation, both from government agencies and consultants, besides traders of course. Everything aims at how the relocation process running smoothly and traders can occupy the new location safely and legally. On this basis, we, the Universitas Harapan Medan Devotion Service Team, conducted socialization activities on Management of Decision Making in Relocating People’s Traditional Market.